2006
DOI: 10.1111/j.1365-2133.2006.07365.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual histopathological features of cutaneous leishmaniasis identified by polymerase chain reaction specific for Leishmania on paraffin-embedded skin biopsies

Abstract: CL seems often to be misdiagnosed clinically in countries where it is not endemic. Histopathologically, CL may be misinterpreted as sarcoidosis, foreign body granuloma, lupoid rosacea and granuloma annulare, especially when Leishmania is not seen microscopically. We suggest that in Northern Europe, PCR for Leishmania-specific DNA should be performed routinely in any granulomatous dermatitis presenting as a single or few nodules on the extremities or face, even when a diagnosis of CL was not considered by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 10 publications
4
57
1
2
Order By: Relevance
“…from a significant number of both single and multiple atypical nodular skin lesions. [1416] From histological point of view, these granulomas, considered “naked” or “sarcoidal granuloma”, are different from the classic tuberculoid granulomas observed in lupus vulgaris and chronic lupoid leishmaniasis, and normally would not be classified as granulomas caused by a living agent. Therefore, organism is either difficult to trace in those chronic lesions or is altogether absent.…”
Section: Discussionmentioning
confidence: 99%
“…from a significant number of both single and multiple atypical nodular skin lesions. [1416] From histological point of view, these granulomas, considered “naked” or “sarcoidal granuloma”, are different from the classic tuberculoid granulomas observed in lupus vulgaris and chronic lupoid leishmaniasis, and normally would not be classified as granulomas caused by a living agent. Therefore, organism is either difficult to trace in those chronic lesions or is altogether absent.…”
Section: Discussionmentioning
confidence: 99%
“…Tedavi bitiminde kontrol kemikiliği biyopsisinde amastigot görülmeyen olguda klinik ve laboratuar olarak yanıt alınmıştır (6). Literatürdeki benzer yayınlara baktığımızda VL gibi kutanöz ve mukokutanöz Leishmaniasis'in de malign hastalıkları taklit edebildiği dikkati çekmektedir (7)(8)(9). Di Cataldo ve ark.…”
Section: Discussionunclassified
“…Başsorgun et al in their study of 28 patients from Turkey in 2015 evaluated the epidermal and dermal changes that would predict the histopathological diagnosis of cutaneous leishmaniasis and found that epidermal thinning/thickening, and orthokeratosis were early stage indicators, while exocytosis, hyperparakeratosis, and epidermal thinning were indicative of late stage disease [18]. Highly unlikely forms of presentation usually show a marked acanthosis or even wide areas of necrosis that can mimic other conditions such as squamous cell carcinoma, deep fungal infection or secondary syphilis, granulomatous lesions (sarcoidal and elastolytic) and simulating lupoid rosacea or granuloma annulare [19,20]. Non specific pathologies which can coexist with cutaneous leishmaniasis include inflammatory diseases (panniculitis, subacute spongiotic dermatitis, lichen planus) or infectious/granulomatous conditions (tuberculosis-like lesions, sarcoidosis, pityriasis lichenoides, indeterminate leprosy), and neoplastic lesions (mycosis, anaplastic T-cell lymphoma).…”
Section: Discussionmentioning
confidence: 99%